Medical students’ perceptions of improving physician satisfaction and patient care: a text network analysis approach - Young Gyu Kwon; Myeong Namgung; Song Hee Park; Mi Kyung Kim; Hyo Hyun Yoo; Chan Woong Kim (BMC Medical Education)
Abstract Background Physicians’ job satisfaction and their relationships with patients are critical factors in modern healthcare. Understanding medical students’ perceptions of these aspects is crucial for enhancing the quality of healthcare. Hence, this study examined medical students’ perspectives on improving physician job satisfaction and the essential patient-oriented attitudes required for developing into skilled physicians. Methods The participants were 87 medical students who provided descriptive essay responses to two open-ended questions: (1) “What do you think could improve physicians’ job satisfaction?” and (2) “What attitudes toward patients do you believe are necessary to become a skilled physician?” Specifically, this study analyzed medical students’ perceptions and attitudes toward physician satisfaction and patient relationships by applying text network analysis to their essay responses and identifying key themes and keywords. Results The major topics were extracted using latent dirichlet allocation topic modeling. Key terms included “physician,” “satisfaction,” “patient,” “medical practice,” and “experience.” Topics identified for the first question included “work–life balance,” “job satisfaction and social impact,” and “satisfaction of physicians in the medical environment.” Topics for the second question included “attitude toward patient care as a physician,” “mistakes in patient care and efforts to correct them,” and “patient care experience and physician skill development.” Conclusions This study aligned educational strategies with self-determination theory (SDT) to underscore the importance of promoting autonomy, relatedness, and competence. This approach could elevate the quality of medical education, support students’ professional growth, and enhance their job satisfaction through meaningful patient interactions.